QOLP-16. CAPTURING THE PRIMARY BRAIN TUMOR (PBT) PATIENT'S EXPERIENCE OF BODY IMAGE DISSATISFACTION: REPORT FROM THE NEURO-ONCOLOGY BRANCH-NATURAL HISTORY STUDY (NOB-NHS). (5th November 2018) - Acquaye, Alvina; Vera, Elizabeth; Aboud, Orwa; Armstrong, Terri; Boris, Lisa; Brown, Miranda; Crandon, Sonja; Garren, Nancy; Ji, Ming; Levine, Jason; Romo, Carlos; Reyes, Jennifer; et al.
Abstract: BACKGROUND: Body image dissatisfaction is associated with difficulty coping and adjustment in patients with other solid tumors. Although PBT patients may be at increased risk due to the visible disfigurement and debilitating nature of the disease, there is limited research in this patient group. The purpose of this report is to present the qualitative analysis of data captured on the NOB-NHS Body Image Study. METHODS: 100 patients participated by completing structured questionnaires and open-ended responses. Seventy-two patients provided open-ended feedback exploring, How have the changes affected you? within the Feedback Form. Qualitative analysis software (MAXQDA) allowed for text coding of response data to identify recurrent themes. RESULTS: The sample was primarily white (82%), males (58%) median age=50 (range 23–74), diagnosed with glioblastoma (36%). Only 10 (8%) indicated no body image issues. Five dominant themes (lifestyle changes, symptom effects, negative & positive outlook, changes in appearance) characterized participant description of body image since their diagnosis. A number of patients (28%) expressed a hindrance within their lifestyle (altered mobility, independence, activity, and changes in relationships) contributing to this theme. Participants described symptom effects (weight gain, fatigue, pain, vision changes) contributing to dissatisfaction throughout the disease trajectory. Specific changes in appearance (hair loss, indentation on head, skin dryness) were also problematic factors affecting adjustment and coping. An ascribed negative outlook (9%) (self-conscious, feeling ashamed or vulnerable) magnified awareness of long-term permanent changes, but some (8%) described the implementation of a positive outlook (using exercise and hope) allowing for acceptance of these changes. CONCLUSION: These findings offer insight from the patients perspective on identified physical, mental and treatment-related factors regarding body image concerns and the scope of issues faced by PBT patients. Understanding patient concerns allows for a multidimensional approach in management of key areas with the goal of improving overall quality of life.